PERAN FAKTOR USIA IBU HAMIL, PARITAS, JARAK ANTARA 2 KEHAMILAN SERTA DAMPAKNYA TERHADAP BERAT BADAN BAYI BARU LAHIR - Purwati, Heni (JURNAL KEPERAWATAN BINA SEHAT, 2011)
Anemia in pregnancy increases the frequency of complications both during pregnancy and labor. It also increases maternal and prenatal mortalities, premature birth, and low birth weight infant. The purposes of this study were to find the difference of maternal age, parity, interval of pregnancy, upper arm circumference, and the birth weight between anemic and non anemic pregnant women.The study design was analytic observational study with cross sectional approach. The research samples were 87 pregnant women with anemia and 87 pregnant women without anemia. These subjects were selected from the register cohort of pregnant women in the working area of Blooto primary health centers at Mojokerto in the period of 1 January 2008 to 30 September 2009. The data recording of pregnant women characteristics and the birth weight is performed to all of the subjects. Data were analyzed using chi square test and the significant rate was determined according to the value of p<0.05.The results of this study indicates that maternal age and parity were not a risk factor. Birth interval < 2 years was the risk factor (RP=2.52). Upper arm circumference < 23.5 cm was the risk factor (RP=2.64). The relation between the incidence of anemia with low birth weight is statistically very significant with p <0.001 and RP = 5.75 (95% CI: 2.89-11.46). Other factors associated with low birth weight besides anemia is the birth interval (OR: 3.0801; 95% CI: 1.143-8.297) and the upper arm circumference (OR: 11.054; 95% CI: 3.951-30.927).In conclusion, birth interval and upper arm circumference are proven to be the risk factor for anemia in pregnancy. Anemia in pregnant women is strongly associated with low birth weight babies.Keywords:maternal age, parity, interval of pregnancy, upper arm circumference, the birth weight, anemia in pregnancy